Mechanical performance of mortars reinforced with steel fibers - Castro Castillo, Matias Renato; Nieto-Cardenas, Jaime Xavier; Illescas-Cardenas, Paul; Naspud Uruchima, Pilar Roxana (EASI: Engineering and Applied Sciences in Industry, 2025)
This article focuses on the evaluation of the resistance of mortars to indirect tension and compression, simple and reinforced, with different percentages of steel fiber. The aim is to find resistant and economical solutions to reinforce informal housing, through the use of plaster that improves the general characteristics of a masonry. Masonry constructed in an informal or artisanal manner has a high degree of structural vulnerability. First, the indirect tensile strength and displacements supported by simple and reinforced mortars are compared, where it is observed that reinforced mortars offer greater strength and deformation capacity as a function of the percentage of fiber. Then, the compressive strength is compared, where the reinforced mortars also show adequate results. In terms of economics, the reinforced mortar presents disadvantages due to the cost of the fibers; in the percentages studied in this article (10, 15, 20 and 25%), the use of reinforced mortars for informal housing is not so attractive; it is recommended to develop similar investigations with different percentages of fiber.